Difficulties in using blended learning from my point of view in the first grade and kindergarten teacher departments in the College of Basic Education (Journal of the College of Basic Education, 2024)
The current research aims to identify (the difficulties of using blended education from the point of view of a teaching teacher in the first grades and kindergarten departments in the College of Basic Education). The limits of the research were represented by it. The researcher used the descriptive approach to achieve the objectives of the research, which is one of the scientific research methods in which the researcher resorted to a number of The procedures included identifying the original population of the study, which consisted of (45) university teachers in the departments of first-grade teachers and childcare in the College of Basic Education at Al-Mustansiriya University. The researcher used the questionnaire as a tool to achieve the objectives of the research. The researcher adopted the open-ended questionnaire and presented it to an exploratory sample of teachers whose number was (20). After sorting the answers and excluding the similar ones, and after reviewing the literature, the researcher came up with the formulation of the questionnaire, which included (25) items. The researcher presented it to a number of experts to calculate its validity and reliability, then applied it to the basic sample of (45) male and female teachers. The results were treated statistically using the mean equation. Weighted and percentage weight. The study showed a set of conclusions, including (the prescribed curriculum is crowded with academic vocabulary), and a set of recommendations, including (distributing students to classrooms in numbers commensurate with the use of blended learning in teaching), and a set of proposals, including (conducting a study on the impact of using blended learning on student achievement. ).